2021
DOI: 10.1371/journal.pone.0260479
|View full text |Cite
|
Sign up to set email alerts
|

Association of small intestinal bacterial overgrowth with nonalcoholic fatty liver disease in children: A meta-analysis

Abstract: It has been suggested that small intestinal bacterial overgrowth (SIBO) could cause nonalcoholic fatty liver disease (NAFLD), but this association was not examined in children by meta-analysis. This meta-analysis aimed to determine the association between SIBO and NAFLD in children. The electronic databases PubMed, Embase, and Cochrane Library were searched for studies published before April 22, 2021. The outcome was the association between SIBO and NAFLD. Three studies and 205 children were included. All thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…As such, liver damage has been found to correlate with the severity of gut dysbiosis [102]. Since a diseased liver cannot effectively remove harmful products from the blood or inhibit the overgrowth of bacteria [103][104][105], this process can accelerate microbiota-gut-brain axis dysregulation and ultimately cognitive decline. Thus, when considering the occurrence of cognitive decline associated with microbial-derived metabolites, the role and function of the liver cannot be ignored.…”
Section: The Microbiota-gut-liver-brain Axismentioning
confidence: 99%
“…As such, liver damage has been found to correlate with the severity of gut dysbiosis [102]. Since a diseased liver cannot effectively remove harmful products from the blood or inhibit the overgrowth of bacteria [103][104][105], this process can accelerate microbiota-gut-brain axis dysregulation and ultimately cognitive decline. Thus, when considering the occurrence of cognitive decline associated with microbial-derived metabolites, the role and function of the liver cannot be ignored.…”
Section: The Microbiota-gut-liver-brain Axismentioning
confidence: 99%
“…A complicating feature for the diagnosis is that these risk factors often appear in other diseases, making SIBO intertwined with other pathologies among which gastroenterological disorders (e.g. inflammatory bowel disease, irritable bowel syndrome, SBS, nonalcoholic fatty liver disease, cirrhosis, diabetes, and cystic fibrosis (Ierardi et al 2016 , Rafiei et al 2018 , Ricci et al 2018 , Fitriakusumah et al 2019 , Ghosh and Jesudian 2019 , Wu et al 2019 , Phyo et al 2021 , Shah 2021 , Feng and Li 2022 , Ghoshal et al 2022 ), and other nongastrointestinal (or indirectly linked) diseases such as Parkinson’s and Alzheimer’s disease (Kuang et al 2021 , Kowalski and Mulak 2022 ).…”
Section: Disruption Of Small Intestinal Homeostasis In Nutrient Balancementioning
confidence: 99%
“…This association was observed in meta-analysis conducted by Wijarnpreecha et al [44]. In another meta-analysis 3 studies were included, which reported that children with SIBO were more likely to have NAFLD [45]. There is also an inverse relationshipincreased prevalence of SIBO is observed in patients with NAFLD [8].…”
Section: Sportsmentioning
confidence: 77%